COMPARATIVE ANALYSIS OF CLINICAL AND LABORATORY PARAMETERS IN PATIENTS WITH GIARDIASIS WITH THE TRADITIONAL METHOD OF TREATMENT. - Khuzhakulov Davron Abdihakimovich (Лучшие интеллектуальные исследования, 2024)
Annotation. Giardiasis is a disease caused by giardia excavators that parasitize the small intestine of humans and some animals. According to WHO, about 200 million people are infected with giardia every year (countries in Asia, Africa, Latin America). The intensive rate per 100,000 population: in Russia - 90.0 (among the total population) and 350.0 (among children under 14 years old); in the USA, Vermont - 42.3, New York State - 20.3 (1992-1997). Clinical manifestations of giardiasis are registered in almost 500 million patients per year worldwide.